Microscopic Image of Sperm Motility and Morphology in A Hospital in Yogyakarta. - Adyatma Teja Kusuma (Universitas Airlangga, 2025)
ABSTRACT Background : Male infertility is reproductive health issues that are getting more attention, one of the reason is the due to the disruption of sperm quality. Sperm motility and morphology becomes important parameters in determining fertility levels Objective : The objective of this research is to understand the microscopic image of sperm motility and morphology on patients in one of the hospital in Yogyakarta. Methods : This research use obervational descriptive design with cross-sectional approach and purposive sampling technique. Sperm analysis done through microscopic examination of 95 samples. Sperm according to WHO in 2021 guidelines. The inspection begins by getting sample after 2-7 prohibition, continued by macroscopic and microscopic analysis according to standard inspection squence from WHO in 2021 Results : The result of this research shows that sample has normal motility by 85,3% and abnormal motility by 14,7%. Moreover, sperm normal morphology covers the form of head, neck, tail, and cytoplasm remains. Patient distribution most happened on the age of 20-39 (93,7%), according to WHO in 2021 as active reproductive age. Conclusion : The research result show that the majority patient getting Asthenzoospermia, by 14,7% has abnormal sperm motility. Teratozoospermia found on 98,9% sample, marked by morphology abnormality on head, neck, tail, and cytoplasm. Keywords : first keyword; Sperm motility, second keyword; Sperm morphology, third keyword; Sperm analysis